Language, Tone, and the Aesthetics of Decay: A Stylistic exploration of Hanif Kureishi’s The Nothing - Gulzar BiBi; Mamona Yasmin Khan (Research Journal of Psychology, 2025)
Hanif Kureishi’s novella The Nothing (2017) offers a poignant and darkly satirical exploration of an aging man confronting mortality, betrayal, and moral disintegration. The current study seeks to examine how language and tone contribute to the aesthetics of decay that permeate the novel. It explores the stylistic features of Hanif Kureishi’s novella The Nothing (2017). It focuses on narrative voice, diction, syntax, and tone. Through a detailed linguistic and stylistic analysis, the study reveals how Kureishi employs language to reflect the protagonist’s psychological deterioration, physical decline, and existential anxieties. The novella, though compact, is rich in literary devices, ironic tonal shifts, and linguistic contrasts that mirror its central themes of aging, jealousy, and betrayal. The paper employs frameworks from stylistics and narrative theory and also illustrates how Kureishi’s language crafts a darkly humorous yet deeply unsettling meditation on human vulnerability.